Subtitusi Mocaf Pada Donat Kentang: Apakah berpengaruh Terhadap Daya Terima Konsumen? - Supriyadi Supriyadi; Arsy Nur Fadilah (Gema Wiralodra, 2022)
This research purpose to find attributes that influence the selection potato donuts made from mocaf and find out the consumer's attitude towards potato donuts made from mocaf. Total respondents in this research are 30 people who had ever bought and ate potato donuts. The respondents were taken by purposive sampling. The methods used in this research is survey methods. The data analysis in this research is using Fishbein Model, the model applied is “the attitude toward object model”. It’s model were used to identify consumer attitudes towards the attributes potato donuts from mocaf and raw material includes taste, texture, shape, color and price suitability. The results show that the most influential attributes in the selection potato donuts made from mocaf are taste (13,74) and color (15,89). Consumer attitudes towards the overall attributes potato donuts are ordinary product. This study recommends potato donut producers to make improvements to the variables of texture, shape and price suitability from consumer input so that it becomes a potato donut product that is preferred by consumers.